Self‐Efficacy in Hypertension Management Using e‐Health Technology: A Randomized Controlled Trial in Primary Care - Rasmus Hermansson‐Borrebaeck; Andreas Fors; Ulrika Bengtsson; Karin Kjellgren; Susanna Calling; Patrik Midlöv (The Journal of Clinical Hypertension)
ABSTRACT Self‐efficacy is tightly intertwined with person‐centered care and correlates with engaging in self‐care behaviors, an important part of hypertension treatment. Evidence indicates that e‐Health‐based self‐management interventions could increase self‐efficacy. The objectives of this study were to investigate whether an intervention with a person‐centered approach supported by e‐Health technology can impact self‐efficacy. Furthermore, to examine the impact of self‐efficacy on hypertension management, and assess if self‐efficacy can indicate which patients might see the greatest improvement on blood pressure from an e‐Health‐based self‐management intervention for hypertension. This multicenter randomized controlled trial included 949 primary healthcare patients with hypertension. After exclusions, data was analyzed for 862 patients. The intervention group used an e‐Health‐based self‐management system for 8 weeks. Self‐efficacy was measured with the general self‐efficacy (GSE) scale at inclusion, 8‐week follow‐up and 1‐year follow‐up. A significant increase in the mean GSE score in the intervention group was identified (p 0.042). No significant association between self‐efficacy and blood pressure control was found. GSE scores did not significantly differ between the patients that had the best effect on blood pressure and those that had none. This study showed a significant increase in self‐efficacy after the intervention. Self‐management‐based e‐Health interventions might have a role in clinical practice to increase self‐efficacy and improve general health. We found no association between self‐efficacy and achieving a blood pressure below 140/90. Furthermore, no support was found to claim that self‐efficacy would be an indicator of which patients might have the greatest effect from a self‐management‐based e‐Health intervention for hypertension.